Neuroinflammatory Markers in Spontaneously Hypertensive Rat Brain: An Immunohistochemical Study - K. Tayebati, Seyed; Tomassoni, Daniele; Amenta, Francesco (CNS & Neurological Disorders - Drug Targets, 2016)
Background: Spontaneously hypertensive rats (SHR) represent a model of hypertension and vascular injury. In the past decade, SHR were also considered as a model of vascular dementia. Several studies have shown that cerebrovascular changes in SHR may mimic brain vascular diseases of hypertensive individuals. Vascular and cerebrovascular changes during hypertension are often linked to inflammatory processes. Inflammation frequently affects vascular endothelium, perivascular astrocytes that form blood brain barrier. This inflammatory reaction may lead to neuro-inflammation with consequent damage of brain tissue. A significant brain atrophy, a reduction of white matter volumes, and BBB dysfunction were found in SHR. Micro- and macrogliosis in deep cortical regions were also observed. Based on these findings, this study was designed to define neuroinflammation entity in SHR, using immunohistochemistry technique for different inflammatory markers. Methods: Thirty-two-week-old SHR and age-matched Wistar Kyoto rats were used. Brain was processed for immunohistochemistry. Astrogliosis markers for astrocytes (glial fibrillary acidic protein) and microglia (isolectin IB4) were used. The pro-inflammatory interleukins (IL-1b, IL-6) and tumor necrosis factor alpha (TNFa) expression were also evaluated. Results: In SHR brain, an obvious glial reaction was found both for GFAP-immunoreactive astrocytes and for microglia. The pro-inflammatory IL-1b was significantly increased in CA1 sub-field of SHR hippocampus. The TNFa expression was higher in frontal cortex of SHR compared to WKY. Conclusion: The above neuromorphological evidences indicate that SHR are predictive animal models for vascular brain disorders and neuroinflammation. Furthermore, this model may be useful to evaluate anti-inflammatory and neuroprotective effects of different molecules.
Keywords: Morphological Analysis